Calculus Assignment 1

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 9

ASSIGNMENT 1

MODULE: CALCULUS
LECTURER NAME: MR ALHASSAN
KOROMA STUDENT NAME: MICHAEL
AMARA
ID NUMBER: 2021110
requirement
Differentiate each one using the various rule

Q1. √ x tan x
Solution
y= √ x tan x

let U= √ x
let V= tan x
1
take U=√ x = x 2

1
dy 1 2−1
= x
dx 2

dy x −1
= 2
dx 2
dy 1 du 1
= 1= = 2
dx dx √ x
2 x2

v= tan x
dv
=sin2 x
dx
dy udv vdu
= +
dx dx dx

dy 1
dx ( )
=( √ x ) ( sin 2 x ) + ( tan x ) 2
√x
dy 2 tan x
\ ANS dx =√ x sin x+
√2 x

Q2. √ x tan x
Solution
y= √ x tan x

1 1
2 2
y=x ( tan x )
1
2
u=x
−1
2
u=x
1
du 1 2
= .x
dx 2
dy 1
=2
dx √ x 1
1
2
v=( tan x )
1
dv 1
= (tanx) 2 sin 2 x .
dx 2
¿ the product rule

dy dv dy
=u +v
dx dx dx
1 −1 1
dy
dx
1
[
=x 2 ( tanx )
2
2
( √1x )
2
]
sin x + ( tanx )2 2

dy 1
dx
=√ x
( √ tanx ) ( √1x )
. sin x + √ tan x
2
2
2

Continuation
dy sin2 x tan x
dx
=√ x 2
(
√ tanx
+
) (√√ )
2
x

dy √ x sin 2 x √ tan x
ANS dx
= 2
√ tan x
+ 2
√x
5
Q3. 1−X

Solution

5
y=
1−x
let u=5∧v =1−x

u=5

dy
=0
dx
v=1−x

dv
=−1
dx
¿ the quitent rtles

du dv
v −u
dy dx dx
=
dx v 2

dy ( 1−x )( 0 ) −(5)(−1)
=
dx (1−x)2
dy 0+5
=
dx (1−x )2

dy 5
=
dx (1−x )
1−x
Q4. 5
Solution
1−x
y=
5
1−x
u=
5
v=1−x
u=1−x
dv
=−1
dx
v=5
dv
=0
dx
dy vdu udv 2
=
dx dx

dx
/v
dy (−1 )− (1−x )( 0 )
=s
dx ( 5 )2
dy −5−0 −5
= =
dx 25 265

dy −1
=
dx 5

Q5. sin 2 X +cos 3


Solution
y=sin2 x +cos 3

dy
=cos ( 2 x ) 2+¿ ¿
dx
dy
=2 cos ( 2 x ) +0
dx
dy
ANS =2 cos 2 x
dx

π
Q6 sin ( 4 θ+ 2 )
Solution
π
(
y=sin 4 θ+
2 )
π
but =90°
2
continuation

y=sin ( 4 θ+ 90° )

recall

sin ( A+ B )=sinAcosB +cosAsinB

sin ( 4 θ+90° )=sin ( 4 θ ) sin 90° +cos ( 4 θ ) sin 90°

sin ( 4 θ+90° )=sin ( 4 θ ) .0+ cos ( 4 θ ) .1

since ,sin 90°=1∧cos 90° =0

°
sin ( 4 θ+90 )=cos ( 4 θ ) =cos 4 θ

y=cos 4 θ

dy
=−4 sin 4 θ

dy
ANS =−4 sin 4 θ

Q7. tanθ+ secθ


Solution
y=tan θ+ secθ

dy
=sec 2 θ+ secθtanθ
dx
dy
ANS =secθ ( secθ +tanθ )
dx

Q8. sin 2 xcos 3 x


Solution
y=sin2 xcos 3 x

let u=sin 2 x∧v=cos 3 x

u=sin 2 x

dy
=2 cos 2 x
dx
v=cos 3 x

dy
=−3 sin 3 x
dx
dy dv du
=u +v
dx dx dx
dy
=( sin 2 x ) (−3 sin 3 x ) + ( cos 3 x ) (2 cos 2 x )
dx
dy
=−3 sin 2 xsin 3 x+2 cos 3 xcos 2 x
dx

ANS 2cos3xcos2x

Q9. sin ( 2 cos 3 x )


Solution
y=si n ( 2cos 3 x )

u=2cos 3 x

dy
=−6 sin 3 x
dx
y=sinu

dy
=cosu
du
chain rule.

dy
=cosu .−6 sin 3 x
du
dy
dx =cos u. -6sin3x
dy
=cos ( 2 cos 3 x ) . (−6 sin 3 x )
dx
dy
ANS =−6 cos ( 2 cos 3 x ) sin3 x
dx

You might also like